PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN MELALUI MODEL PROBLEM BASED LEARNING PADA SISWA KELAS V UPT SD NEGERI 067241 MEDAN DENAI - Eliezer Siringoringo; M Fauzi Hasibuan; Helmida Sitanggang (STKIP Subang, 2024)
This study focuses on the low learning outcomes in mathematics, specifically on the topic of fraction addition and subtraction, in the 5th grade at UPT SD Negeri 067241 Medan Denai. The research aims to improve students' learning outcomes through the implementation of the Problem Based Learning (PBL) model. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which includes four stages: planning, action, observation, and reflection.The subjects of this study were 25 students of the 5th grade. Data collection was carried out through tests, and the results showed a significant improvement in learning outcomes after the application of PBL. Before the action, only 58% of the students met the Criteria for Achievement of Learning Outcomes (KKCP). After implementing PBL and using teaching aids, this percentage increased to 69% in the first cycle and reached 86% in the second cycle. The average student score also increased from 58.96 in the pre-action phase to 69.40 in the first cycle, and 85.80 in the second cycle.